Effectiveness of Media in Mobilizing People towards Social Causes and Campaigns - Mendiratta, Ankita; Mehta, Vinayak (Indian Journal of Marketing, 2011)
Purpose- To understand and analyze the extent to which media mobilizes and impacts people to take action for any social campaign, analyze and determine the most effective media for making a campaign a success, and the appropriate frequency and media channel for conducting a social campaign. Design/methodology/approach - An online survey was floated across people across various age groups through emails. The questionnaire consisted of questions ranging from demographics, media exposure, campaign awareness, campaign impact, to campaign participation. The results of this questionnaire were analyzed using the four-step method for mediation analysis. The study also analyzed the role of two moderators - gender and exposure to media of the respondents. Findings - Both, type of media and brand shift are directly related to the effectiveness of a social campaign, but the relationship between the type of media and impact of a campaign is not mediated by the brand shift. Practical implication - Likely implications of this research survey and the corresponding output measurements would have benefits for the people who are to run the social campaigns in the future. The benefits would be: • A correlation between the type of media and the type of campaign which could help to determine the type of media best suited for a particular campaign. • Appropriate frequency and the length for conducting the campaign in the appropriate media to have the desired effect. • The amount of Brand building that results for a particular media, if the campaign is successful. Limitations-A cross sectional, self reporting questionnaire prohibited the understanding of causal relationships between different attributes. The survey responses may have been affected by the social desirability bias. There was not the desired variation in respondents' demographics. Originality/value - Various campaigns have been done to test the media effectiveness. In marketing campaigns, however, this is one of its kind surveys to determine the effectiveness of media in mobilizing people towards social causes and campaigns.